Neurocognitive evaluation using the International HIV Dementia Scale (IHDS) and Montreal Cognitive Assessment Test (MoCA) in an HIV‐2 population. Issue 3 (4th October 2020) - Almeida, F; Macedo, A; Trigo, D; Abreu, M; Guimarães, M; Luís, N; Pinho, R; Tavares, R
Abstract : Objectives: We aimed to characterize neurocognitive impairment (NI) in an HIV‐2 population using an observational cross‐sectional study in four Portuguese hospitals. Methods: Adult HIV‐2‐infected patients were included. Montreal Cognitive Assessment Test (MoCA) and International HIV Dementia Scale (IHDS) scales were applied for screening of NI. Patient Health Questionnaire‐9 (PHQ‐9) and Instrumental Activities of Daily Living (IADL) scales were used for assessment of depression and functionality. A multivariate analysis was performed to assess for risk factors for NI. Results: Eighty‐one patients were included, 50.6% of African origin ( n = 41) and 49.4% of Portuguese origin ( n = 40). The MoCA scale showed alterations in 81.5% of patients (100% of migrants vs . 62.5% of non‐migrants, P < 0.001) and the IHDS scale showed alterations in 42%. Both scales were altered simultaneously in 35.8%. Variables independently associated with NI were age [odds ratio (OR) = 0.885] and migrant status (OR = 9.150). Conclusions: Neurocognitive impairment (both scales altered) was present in 35.8%, which is comparable to what is described for HIV‐1. The MoCA performed worse in the migrant population and might not be applicable in this setting.